Numerical study on heat transfer characteristics of heat exchange cell in an annular cross-wavy primary surface recuperator (annular CWPSR). (5th November 2022) - Yang, Yanzhao; Chen, Fu; Yu, Jianyang; Song, Yanping; Hu, Handuo; Xu, Dongqiang; Jiang, Huadong
Highlights: The heat transfer coefficient of SCC is higher than that of HEC. The heat transfer of HEC is mainly carried out in the CW channel structure. The temperature distribution of inlet section of air and gas CW channel is uneven. The thermodynamic characteristics vary in different CW channels. Effect of AIS on heat transfer coefficient of CA01 decreases with the increase of Re. Abstract: To eliminate the deficiency arising from the whole machine test with simplified cross-wavy (SCC) in investigating the impact of inlet and outlet structure and heat transfer characteristics of different channels, the heat exchange cell (HEC) is employed to explore the heat transfer and flow mechanism of the annular cross-wavy primary surface recuperator (CWPSR). In this work, we propose a complex physical model of HEC corresponding to the real geometric structure of the annular CWPSR, and establish the three-dimensional numerical simulation of fluid-thermal-structural coupling. By numerical simulation, we compare the thermodynamic characteristics between the HEC and SCC, and we analyze the temperature distribution of the HEC and the cross-wavy (CW) channel inlet section, as well as the heat transfer characteristics along flow direction for the different CW channels. The results show that there is a significant difference in thermodynamic characteristics between the HEC and SCC. Meanwhile, the heat transfer coefficient of CW channel structure is higher compared with the inlet and outlet structure for the HEC. In addition, the temperature of the air and gas CW channel inlet section increases gradually from the base circle R 1 to the outer circle R 2 . Because of the existence of the air and gas inlet structure, the temperature of the CW channel increases from Channel-5 to Channel-30.